Penal welfarism ‘gone global’? Comparing international criminal justice to The Culture of Control - Lohne, Kjersti (Punishment & society, 2021)
With the consolidation of a cosmopolitan field of international criminal justice, penality has ‘gone global’. In spite of the abundance of doctrinal legal analysis, human rights studies, and transitional justice studies, there are few analytic attempts to engage with the working assumptions, cultural commitments, and dominant mentalities that give shape to international criminal justice as a penal field. Based on ethnographic observations, interviews with key actors, and critical reading of international criminal justice scholarship, this article compares the cosmopolitan penality of international criminal justice to that of late modern, domestic, penality. Using David Garland’s The Culture of Control as an analytic yardstick, it argues that international criminal justice both resembles and departs from ‘the national’. For example, whilst the cosmopolitan penality relies upon retributive justifications, it makes no appeal to harsh penal sanctions; nor is it concerned with the rehabilitation of prisoners. Rather, it is an expressive and humanitarian form of justice where the victim takes central stage – as the embodiment of a suffering humanity. Moreover, there is a remarkable faith in the transformative effects of international criminal justice, resembling a form of penal welfarism ‘gone global’. As national capacity building and penal development has become intrinsic to the project of international criminal justice, the article shows how the global dimension of the power to punish is based on a moralization of politics.